Lack of association between chronic exposure to biomass fuel smoke and markers of right ventricular pressure overload at high altitude - Caravedo, Maria A. (Am Heart J, 2014)
BACKGROUND: Chronic exposure to biomass fuel smoke has been implicated in the development of pulmonary hypertension and right ventricular pressure/volume overload through activation of inflammation, increase in vascular resistance and endothelial dysfunction. We sought to compare N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) and echocardiography-derived pulmonary artery systolic pressure (PASP) levels in a high-altitude population-based study in Peru with and without chronic exposure to biomass fuel smoke. METHODS: NT-pro-BNP levels were measured in 519 adults (275 with and 244 without chronic exposure to biomass fuel smoke). Participants answered sociodemographics and clinical history questionnaires, underwent a clinical examination and blood testing for cardiopulmonary biomarkers. PASP was measured in a subgroup of 153 (31%) subjects. RESULTS: The study group consisted of 280 men (54%) and 239 women (46%). Average age was 56 years and average body mass index was 27 kg/m(2). In multivariable analysis, there was no association between chronic exposure to biomass fuel smoke and NT-pro-BNP (p=0.31) or PASP (p=0.31). In the subgroup in which both NT-pro-BNP levels and PASP were measured, there was strong evidence of an association between these two variables (ρ=0.24, 95% CI 0.09-0.39; p=0.003). We found that age, high sensitivity C-reactive protein, being male and systolic blood pressure were positively associated with NT-pro-BNP levels whereas body mass index, LDL/HDL ratio and HOMA-IR were negatively associated (all p<0.01). CONCLUSIONS: In this population-based study in a high-altitude setting, neither NT-pro-BNP levels nor echocardiography-derived PASP were associated with chronic exposure to biomass fuel smoke.